2020
DOI: 10.1021/acsnano.0c07999
|View full text |Cite
|
Sign up to set email alerts
|

Universal in Situ Crafted MOx-MXene Heterostructures as Heavy and Multifunctional Hosts for 3D-Printed Li–S Batteries

Abstract: The Li–S battery has emerged as a promising next-generation system for advanced energy storage. Notwithstanding the recent progress, the problematic polysulfide shuttling, retarded sulfur redox, and low output of volumetric capacity remain daunting challenges toward its practicability. In response, this work demonstrates herein a universal approach to in situ craft MO x -MXene (M: Ti, V, and Nb) heterostructures as heavy and multifunctional hosts to harvest good battery performances with synchronous polysulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 49 publications
0
66
0
Order By: Relevance
“…We revealed that Δ E , Δ E (*LiS), and ICOHP can serve as distinguished descriptors for rationally designing potential catalysts of MN 4 @G catalyzing Li 2 S decomposition and next we extended this strategy to predict the catalytic performance of various types of 2D materials with dispersed atomic metals for Li 2 S decomposition. Recently, various strategies have been proposed to enhance the catalytic performances of SACs toward electrochemical reactions, which involve heterostructures [ 51 , 52 , 53 ] and heteroatoms dopants other than N to tailor the local atomic environments. [ 54 ] Therefore, we used Δ E , Δ E (*LiS), and ICOHP to search for enhanced catalytic performance compared to WN 4 @G and MoN 4 @G by introducing interface effect and S dopant to modulate electronic properties of active metal center.…”
Section: Resultsmentioning
confidence: 99%
“…We revealed that Δ E , Δ E (*LiS), and ICOHP can serve as distinguished descriptors for rationally designing potential catalysts of MN 4 @G catalyzing Li 2 S decomposition and next we extended this strategy to predict the catalytic performance of various types of 2D materials with dispersed atomic metals for Li 2 S decomposition. Recently, various strategies have been proposed to enhance the catalytic performances of SACs toward electrochemical reactions, which involve heterostructures [ 51 , 52 , 53 ] and heteroatoms dopants other than N to tailor the local atomic environments. [ 54 ] Therefore, we used Δ E , Δ E (*LiS), and ICOHP to search for enhanced catalytic performance compared to WN 4 @G and MoN 4 @G by introducing interface effect and S dopant to modulate electronic properties of active metal center.…”
Section: Resultsmentioning
confidence: 99%
“…218 Though the poor performance was attained due to the low electric conductivity of sulfur copolymer, this work indeed motivated tremendous efforts on regulating the employed ink and architecture for realizing sulfur loading cathodes with 3D printing. Subsequent works such as improving the conductivity of ink 217 or tailoring thickness and pores 219 were also reported. Impressively, a versatile 3D printed N-doped porous Ti 3 C 2 MXene framework was fabricated by Sun and coworkers.…”
Section: Spray-dryingmentioning
confidence: 99%
“…Recently, Wei et al introduced a metal oxide/MXene heterostructure for 3D-printed Li-S batteries. [153] Using a hydrothermal approach, they synthesized in situ MO x /MXene (M: Ti, V, Nb) heterostructures as S host. The heterostructure acted as a multifunctional host providing abundant active sites for Li 2 S n adsorption and catalytic activity.…”
Section: Li-s Batteriesmentioning
confidence: 99%